2001
DOI: 10.1016/s1381-1169(00)00470-2
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of vanadyl pyrophosphate: cluster model studies

Abstract: The electronic properties of (VO) 2 P 2 O 7 (1 0 0) surface are discussed using the cluster model and DFT method. The calculations indicate that present cluster models are size converged and the cluster as large as V 10 P 6 O 50 H 30 can be considered the realistic model of the extended (VO) 2 P 2 O 7 (1 0 0) surface. Vanadyl pyrophosphate forms a material of a mixed ionic-covalent character. Major covalent contributions participate in the V-O as well as in the P-O binding. The calculations reveal clear electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…Moreover, as reported earlier higher amounts of surface lattice oxygen, which act as active species are also contributed in improving the catalyst activity [30]. The results revealed that the specific oxygen species was highly active for partial oxidation of n-butane and agreed with the electrical conductivity data obtained by Hermann and co-workers [31].…”
Section: Catalytic Oxidation Of N-butanesupporting
confidence: 89%
“…Moreover, as reported earlier higher amounts of surface lattice oxygen, which act as active species are also contributed in improving the catalyst activity [30]. The results revealed that the specific oxygen species was highly active for partial oxidation of n-butane and agreed with the electrical conductivity data obtained by Hermann and co-workers [31].…”
Section: Catalytic Oxidation Of N-butanesupporting
confidence: 89%
“…Witko et al [151,152] reported about DFT calculations of the electronic structure for different clusters modelling a defective VPP (100) surface. It was found that neutral isolated oxygen vacancies may act as sources for enhancing the activity and selectivity of VPO.…”
Section: In-situ Investigation and Modelling On The Nature Of Vpp Actmentioning
confidence: 99%
“…Among many examples in catalysis, the theoretical investigations on the structural and electronic surface properties and the catalytic reactions of transition-metal oxides, in particular based on vanadium and molybdenum, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] are especially important as they provided a deep insight into the structure-activity relationship of these compounds, used in a variety of applications.…”
Section: Introductionmentioning
confidence: 99%